Genome analysis of Lysinibacillus sphaericus isolate 6.2 pathogenic to Culex quinquefasciatus Say, 1823 (Diptera: Culicidae) - Afiannisa Viersanova; Hari Purwanto (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Viersanova A, Purwanto H. 2021. Genome analysis of Lysinibacillus sphaericus isolate 6.2 pathogenic to Culex quinquefasciatus Say, 1823 (Diptera: Culicidae). Biodiversitas 22: 5211-5222. Lysinibacillus sphaericus is an entomopathogenic bacteria that is specific to vector mosquitoes, especially Culex spp., and Anopheles spp., so it has been widely used as a bioinsecticide. L. sphaericus has a wide variation of toxicity efficiencies, which have led to continuous exploration of new isolates with higher toxicity and a new toxin to deal with resistance problems. This study aimed to identify the genomic characteristics and toxin characteristics of isolate 6.2 based on whole genome analysis and analyze the identification of isolate 6.2. Isolate 6.2 was previously obtained from rhizosphere in Yogyakarta. To analyze the genome and toxins, the NGS technique was used and then the analysis was carried out using a couple of freely available bioinformatics tools. Molecular identification was carried out with the 16SrRNA gene and the relationship was analyzed by reconstructing the phylogenetic tree using Neighbours-Joining. The genomic analysis of isolate 6.2 showed good results with G+C content and genome size that matched the reference genome of L. sphaericus. The result of the 16SrRNA gene blasting showed that the closest related gene of isolate 6.2 is L. fusiformis (NR_042072.1). However, the reconstructed phylogenetic tree did not show the formation of clusters according to the species. Toxin analysis indicates that isolate 6.2 has Mtx, s-layer protein, hemolysin, and chitin-binding protein genes. All of which are known to be associated with the toxicity of L. sphaericus to binary toxin resistant population of Culex quinquefasciatus.